ANALYSIS OF THE PAYMENT COVERAGE AT PT. JASA RAHARJA IN BANDA ACEH ACCORDING TO THE CONCEPT OF KAFALAH - Maulana, Muhammad; Fadila, Alifa (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
The risks that often occur in accidents tend to vary from the mildest accidents to those that take lives. In this case, PT. Jasa Raharja has entered into an agreement with the participants about the type of risk and the premium level that will be given when the risk occurs. However, in some cases, there tends to be a difference in the form of claims made by the participants to the coverage provided by PT. Jasa Raharja so that it can harm the participants who have paid the premium. This thesis is focused on answering three important things, 1) How to assess the condition of the object of coverage for the submission of insurance claims at PT. Jasa Raharja, 2) How is the calculation and determination of the accident insurance value determined by the management of PT. Jasa Raharja Banda Aceh on the risks experienced by participants, 3) What is the perspective of the concept of kafalah on the calculation of the accident insurance value at PT. Jasa Raharja. This research is a qualitative research that is descriptive analysis with a sociological normative approach, where the data obtained is sourced from the results of observations and interviews. The results of the study show that, first, the assessment of the condition of the insured object is categorized into three main groups, namely: treatment (injuries), permanent disability, and death. Second, the value of coverage provided by PT. Raharja services vary according to the risk experienced by participants when an accident occurs. Third, the coverage carried out by PT. Raharja's services to traffic accident victims are in accordance with the concept of kafalah that has been explained by the jurists in the fiqh of muamalah regarding the coverage carried out by third parties against risks that occur based on the agreement of the first, second and third parties. However, in the concept of kafalah, there is no maximum of the amount of insurance costs that must be borne by the kafil for makful'ahu.